(3VjGA GdMdhe GdeNJUQ ef TeS GdYdhes - (3eMeO Hf fThGf Hf SYjO Hf fThGf GdMejQi Gdjefi , J (B610 (3g` s; (3fThGf GdMejQj , fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3cJGH GdUGO , HGH GdUGO heG HYOgG ef GdMQha ai GdeVGYa s
(3BNQgG (B:s
(3JfJgi CKfGA ChGFd cJGH GdbGa hBNQ GdehLhO efgG , bhdg bWQ GdeGA bWQkG hbWQGfkG hbWQJg , jJYOi s
(3GdLRA GdKGdK ef GdfSNI GdNGeSI fSNI GdMQe Gdeci (B105s
(3GdfSNI KGdKI eVWQHI GdJQJjH hHHYV ChQGbgG WeSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
Keywords: (3GddZIs